Children are no match for fire : a fire safety story for the whole family - Dean, Carol; Dunn, Sandra (Washington, D.C. : National Association of State Fire Marshalls, 2006)
John and Jodie are twins who are turning five years old on July 4th. They attend a class at their local fire department where Patches, the department's dalmatian, shows them his version of Stop, Drop, and Roll. The twins are eager to share what they have learned with their parents and want to practice the things Chief Foley had suggested. Little did they know how important the training was going to be to their friend Kim. John and Jodie have a brithday they will never forget. John becomes a hero and receives an award for his quick action.
Keywords: Fire prevention -- Children -- Juvenile literature